Reclaiming Singapore's Lost Soul - An interview with Stanley Tan - Lien Centre for Social Innovation (Institutional Knowledge at Singapore Management University, 2012)
As Singapore’s volunteer chief, Stanley Tan has been championing a more active citizenry and finding back the lost soul of Singapore. Social Space catches up with the chairman of the National Volunteer & Philanthropy Centre (NVPC) for his insights on Singaporeans and the social sector.